The Effectiveness Of Lesson Study On Differentiated Instruction Among Mathematics Head Panels In District Of Port Dickson - Ping, Lau Sai; Ameer Hamza, Ilda Salwani binti; Abdullah, Ruzihan binti; Yasin, Murni binti Mohamad; Sooria, Suzalin binti Zaini; Bee, Lee Bee (Postulat : Jurnal Inovasi Pendidikan Matematika, 2020)
This study is to examine the effectiveness of lesson study on differentiated instruction among Mathematics head panels in district of Port Dickson, Malaysia. Teachers who received substantial professional development can boost their students’ achievement. The effectiveness of professional development practice is being measured by the heads of panel understanding about differentiated instruction and the application of differentiated instruction in the classroom. Teachers often struggle to deliver mathematics lesson effectively in classroom due to different learning styles and students’ mixed abilities in the classroom. Some students learn at a slower pace and some in advance stage. The activities provided by teachers may work best for some students but will not work for others. During lesson, teachers often assign tasks, which many students end up with disappointment and confusion. Students become passive learners and teacher felt frustrated. Therefore, differentiated instructions make sense because it offers different paths to understand content, process and product. The aim of the present study was to obtain information from the school teachers in the implementation and planning of differentiated instruction in teaching and learning. Moreover, the research team were interested in knowing the strategy of differentiated instruction used in teaching and learning that support quality teaching. This study involved 33 mathematics head panels from national primary schools in district of Port Dickson who volunteered to participate in this study. In this programme, heads of panel will be able to share their experiences in conducting and implementing differentiated instructions in classroom among peers in the district. Structured questionnaires and interviews were used in this qualitative study to collect data. Results indicated that the lesson study carried out by the Port Dickson District Education Office is effective. Furthermore, the lesson study that were carried out by heads of panel in theirs school managed to boost self confidence among these heads of panel. In fact, they showed willingness to share best practices to all mathematics teachers in the district 205